'We are labeled as gang members, even though we are not': belonging, aspirations and social mobility in Cartagena. (1st January 2018) - Marzi, Sonja
ABSTRACT: This paper explores how belonging and aspirations interact to shape marginalized young Colombians' strategies for upward social mobility. Recent literature has argued that in the context of inequality and poverty, social mobility is constrained by people's inability to aspire to and/or achieve their aspirations. The majority of this literature is from the economics field and looks at the way poverty acts as a brake on social mobility. This paper provides an additional interdisciplinary analysis of the role of 'belonging' (to places and social class) in influencing aspirations of young Colombians. Findings are based on ethnographic fieldwork with young people from two marginalized neighborhoods in Cartagena. It is argued that aspirations are closely linked to belonging and the extent to which young people feel integral to or distanced from their localities. Using a Bourdieusian perspective, the paper examines how belonging is developed and how it influences behavior, orientations and future prospects. This approach generates insights into young people's apparent low aspirations beyond the explanation of internal behavioral poverty traps. In so doing, it provides a more comprehensive understanding of how societal structures limit aspiration development and achievement.